Prototype of a Solar Collector with the Recirculation of Nanofluids for a Convective Dryer - Denis Del Sagrario Garcia-Marquez; Isaac Andrade-Gonzalez; Arturo-Moises Chavez-Rodriguez; Mayra I Montero-Cortes; Vania Sbeyde Farias-Cervantes (International Journal of Renewable Energy Development, 2022)
Solar collectors are thermal devices that can trap solar energy and convert it to heat. This heat can be used for different industrial applications, for example, the drying of food is one of the most useful applications of solar collectors. This work aims to design and build a solar collector using nanofluids for the convective drying of food. The dimensions of the solar collector were 1 m2 by 20 cm with an angle of inclination of 45°. The collector was composed of 9-mm thick tempered glass and a heat exchanger in which the nanofluids circulate. Nanofluids were designed based on canola oil and nanopowders (>50 nm) of Al2O3, CuO, and a 1:1 (w/w) mixture of both. Thermal profiles were determined using differential scanning calorimetry (DSC). The solar collector temperatures were recorded using an Agricos® unit. The maximum temperatures of the air leaving the collector were 39.1°C, 44°C, 54°C, and 47.1°C for canola oil, and the nanofluids composed of Al2O3, CuO, and the 1:1 mixture, respectively, with a maximum efficiency of 65.09%. An increase in the outlet air temperature was observed using the nanofluids compared to canola oil alone